Timing of Communication. Issue 630 (14th April 2020) - Bhattacharya, Puja; Nielsen, Kirby; Sengupta, Arjun
Abstract: Using an experiment, we demonstrate that a communication regime in which a worker communicates about his intended effort is less effective in: ( i ) soliciting truthful information; and ( ii ) motivating effort than one in which he communicates about his past effort. Our experiment uses a real-effort task, which additionally allows us to demonstrate the effects of communication on effort over time. We show that the timing of communication affects the dynamic pattern of work. In both treatments, individuals are most co-operative closest to the time of communication. Our results reveal that the timing of communication is a critical feature that merits attention in the design of mechanisms for information transmission in strategic settings.